Implementing Obstetric Venous Thromboembolism Protocols on a Statewide Basis: Results from New York State's Safe Motherhood Initiative - Friedman, Alexander M.; Ananth, Cande V.; Lavery, Jessica A.; Fleischer, Adiel A.; Chazotte, Cynthia; D'Alton, Mary E.; for the Safe Motherhood Initiative Venous Thromboembolism Work Group; Berkowitz, Richard; Brodman, Michael; Brown, Barry; Christakis, Christa; Combs, Adriann; Eddleman, Keith; Klein, Victor; Minkoff, Howard; Shilkrut, Alexander; Silverman, Robert; Sylvestre, Georges; Vintzileos, Anthony; Waldman, Richard; Wilcox, Wendy (American Journal of Perinatology, 2019)
Objective To determine whether a state-level initiative to reduce obstetric venous thromboembolism (VTE) risk affected outcomes and process measures.Methods In 2013, the Safe Motherhood Initiative (SMI) developed a VTE safety bundle to reduce obstetric VTE risk. A total of 117 of 124 hospitals providing obstetrical services in New York participated in SMI. Data evaluating thromboembolism events (deep vein thrombosis and pulmonary embolism) and thromboprophylaxis process measures were collected from March through November 2015.Results A total of 107 hospitals, in any individual quarter, reported data on each of the VTE bundle outcomes and measures. Centers that provided low-risk care (Level 1 centers) reported the lowest rate of bundle implementation at the end of the study period (55.6%). Mechanical prophylaxis for a cesarean was common at all centers. Hospitals that adopted the bundle were more likely to provide routine pharmacologic prophylaxis for women undergoing cesarean. The risk of VTE did not differ by bundle implementation.Conclusion While adoption of the SMI VTE bundle occurred at a majority of centers across New York, uptake was less likely at low-acuity centers. Bundle adoption was associated with implementation of recommended practices. The rare nature of VTE events underscores the need for large data samples to determine the best prophylaxis strategies.
Keywords: obstetric thromboembolism; thromboembolism prophylaxis; maternal mortality; Safe Motherhood Initiative